Вплив наночасток оксиду заліза на термічну деструкцію адсорбованого на кремнеземі поліметилфенілсилоксану - Bogatyrov, V. M.; Galaburda, M. V.; Pokrovskiy, V. A.; Mischanchuk, B. G. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
Method of temperature-programmed desorption mass spectrometry was used in studies on thermal destruction of polymethylphenylsiloxane on the surface of fumed SiO2 and of nanocomposite Fe2O3/SiO2 with various ratio of components. Bensene evolution (78 a.u.) with Tmax at 500-580°C and methane (16 a.u.) with Tmax at 680-700 °C was observed for silica surface. In presence of Fe2O3 essential decrease of benzene evolution was took place, accompanied by loss of extremal shape of temperature dependence. Effect of thermal treatment conditions on thermal destruction of adsorbed molecules was considered.